2019
DOI: 10.3390/ma12244210
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Study of Electronic Transport in Monolayer InSe

Abstract: The absence of a band gap in graphene makes it of minor interest for field-effect transistors. Layered metal chalcogenides have shown great potential in device applications thanks to their wide bandgap and high carrier mobility. Interestingly, in the ever-growing library of two-dimensional (2D) materials, monolayer InSe appears as one of the new promising candidates, although still in the initial stage of theoretical studies. Here, we present a theoretical study of this material using density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…The electron transport in various 2D materials and devices have been widely studied using different theoretical/computational methods, including Monte Carlo (MC), Wigner equation, nonequilibrium Green's functions, and master equation for the density matrix [14][15][16]. Particularly, the MC method has been applied to study silicene and germanene, [17] InSe, [18] and graphene. [19][20][21][22][23] Regarding the high-field electron transport in MX2, Ferry [24] studied MoS2 and WS2 using MC method: the electron band structure and the scattering rates approximated by analytic models with parameters taken from first-principles calculations and experiments; MoS2 is found to have a higher saturation velocity than WS2.…”
Section: Introductionmentioning
confidence: 99%
“…The electron transport in various 2D materials and devices have been widely studied using different theoretical/computational methods, including Monte Carlo (MC), Wigner equation, nonequilibrium Green's functions, and master equation for the density matrix [14][15][16]. Particularly, the MC method has been applied to study silicene and germanene, [17] InSe, [18] and graphene. [19][20][21][22][23] Regarding the high-field electron transport in MX2, Ferry [24] studied MoS2 and WS2 using MC method: the electron band structure and the scattering rates approximated by analytic models with parameters taken from first-principles calculations and experiments; MoS2 is found to have a higher saturation velocity than WS2.…”
Section: Introductionmentioning
confidence: 99%
“…Each I EFF data point is obtained with an applied V DD = 0.75 V after aligning all I D ‐ V GS curves at I OFF = 2 × 10 −3 μA μm −1 ( V GS = 0 V). Filled symbols (circle [ 42 ] and square [ 43 ] ) refer to the theoretical phonon‐limited mobility of monolayer 2D materials solved by the BTE with EPC matrix elements from first‐principles calculations. Open symbols refer to the theoretical phonon‐limited mobility of monolayer 2D materials calculated by Takagi formula [ 48 ] with effective deformation potential and mass extracted from first‐principles (triangles, [ 44 ] cross, [ 45 ] square, [ 46 ] and diamonds [ 47 ] ).…”
Section: Materials Fundamental Parameters: Proxies For Device Performancementioning
confidence: 99%
“…[ 46,101 ] However, due to the lack of center of inversion symmetry, a recent full‐band Monte–Carlo calculation has shown that the mobility of monolayer InSe is around 100 cm 2 V −1 s −1 with the long‐range electron–phonon interaction considered. [ 43 ] Even with this electron mobility, monolayer InSe still keeps good performance contributed to its small effective mass for short gate length transistors. But, a “Mexican hat” shape‐like valence band structure with low dispersion leading to a very large hole effective mass makes the monolayer InSe unsuitable for p‐type transistor applications.…”
Section: Selection Of 2d Materialsmentioning
confidence: 99%
See 2 more Smart Citations